The role of innate immune cells in the colorectal cancer tumor microenvironment and advances in anti-tumor therapy research - Liu, Wenxuan; Kuang, Tianrui; Liu, Li; Deng, Wenhong (Frontiers in Immunology, 2024)
Innate immune cells in the colorectal cancer microenvironment mainly include macrophages, neutrophils, natural killer cells, dendritic cells and bone marrow-derived suppressor cells. They play a pivotal role in tumor initiation and progression through the secretion of diverse cytokines, chemokines, and other factors that govern these processes. Colorectal cancer is a common malignancy of the gastrointestinal tract, and understanding the role of innate immune cells in the microenvironment of CRC may help to improve therapeutic approaches to CRC and increase the good prognosis. In this review, we comprehensively explore the pivotal role of innate immune cells in the initiation and progression of colorectal cancer (CRC), alongside an extensive evaluation of the current landscape of innate immune cell-based immunotherapies, thereby offering valuable insights for future research strategies and clinical trials.